Functional and anatomical correlates in atrial septal defect. An echocardiographic analysis. Issue 2 (August 1985) - Forfar, J C; Godman, M J
Abstract : The results of cross sectional echocardiography, intracardiac contrast echocardiography, and balloon sizing techniques and conventional haemodynamic assessment were correlated in 40 consecutive patients evaluated for an isolated left to right shunt at atrial level. Echo free areas along the septum were identified in 23 of 25 patients with a secundum defect, but not in two with a fenestrated defect, and in the upper atrial septum in three of four patients with a sinus venosus defect. No false positive results occurred in 11 patients with a probe patent foramen ovale. Saline contrast injection into the left atrium showed significant left to right shunting in all patients with atrial septal defect; inferior vena caval injection produced right to left shunting in 15 of 29 patients and a negative contrast effect in eight of 29 patients with an atrial septal defect, although neither correlated quantitatively with defect diameter or magnitude of the left to right shunt. Echocardiographic assessment of defect size as small, moderate, or large showed a highly significant correlation with balloon measurement of defect diameter, although some overlap between the groups was evident. In contrast, the correlation between defect diameter and pulmonary to systemic blood flow ratio was poor, mainly because of highly variable shunting in patients with an anatomically large defect. Cross sectional echocardiography has high sensitivity and specificity in the diagnosis of the non-fenestrated atrial septal defect and provides quantitative information about defect diameter. Contrast studies do not add to the diagnostic value of imaging from the subcostal position. The poor correlation between defect size and the measured shunt suggests that the latter may not be the best criterion for surgical management and that size could be an important factor likely to influence both the long term prognosis and the decision for closure.